Major Adverse Cardiac Events and Mortality Associated with Electroconvulsive Therapy: A Systematic Review and Meta-analysis. (January 2019) - Duma, Andreas; Maleczek, Mathias; Panjikaran, Basil; Herkner, Harald; Karrison, Theodore; Nagele, Peter
Editor's Perspective: What We Already Know about This Topic: The incidence of major adverse cardiac events after electroconvulsive therapy is not known What This Article Tells Us That Is New: Major adverse cardiac events and death after electroconvulsive therapy are infrequent and occur in about 1 of 50 patients and after about 1 of 200 to 500 electroconvulsive therapy treatments Background: Cardiac events after electroconvulsive therapy have been reported sporadically, but a systematic assessment of the risk is missing. The goal of this study was to obtain a robust estimate of the incidence of major adverse cardiac events in adult patients undergoing electroconvulsive therapy. Methods: Systematic review and meta-analysis of studies that investigated electroconvulsive therapy and reported major adverse cardiac events and/or mortality. Endpoints were incidence rates of major adverse cardiac events, including myocardial infarction, arrhythmia, pulmonary edema, pulmonary embolism, acute heart failure, and cardiac arrest. Additional endpoints were all-cause and cardiac mortality. The pooled estimated incidence rates and 95% CIs of individual major adverse cardiac events and mortality per 1, 000 patients and per 1, 000 electroconvulsive therapy treatments were calculated. Results: After screening of 2, 641 publications and full-text assessment of 284 studies, the data of 82 studies were extracted (total n = 106, 569 patients; n = 786, 995 electroconvulsive therapy treatments). The most commonly reported major adverse cardiac events were acute heart failure, arrhythmia, and acute pulmonary edema with an incidence (95% CI) of 24 (12.48 to 46.13), 25.83 (14.83 to 45.00), and 4.92 (0.85 to 28.60) per 1, 000 patients or 2.44 (1.27 to 4.69), 4.66 (2.15 to 10.09), and 1.50 (0.71 to 3.14) per 1, 000 electroconvulsive therapy treatments. All-cause mortality was 0.42 (0.11 to 1.52) deaths per 1, 000 patients and 0.06 (0.02 to 0.23) deaths per 1, 000 electroconvulsive therapy treatments. Cardiac death accounted for 29% (23 of 79) of deaths. Conclusions: Major adverse cardiac events and death after electroconvulsive therapy are infrequent and occur in about 1 of 50 patients and after about 1 of 200 to 500 electroconvulsive therapy treatments. Abstract : Major adverse cardiac events and death after electroconvulsive therapy are infrequent and occur in about 1 of 50 patients and after about 1 of 200 to 500 electroconvulsive therapy treatments.Supplemental Digital Content is available in the text.